Keberlanjutan Pengelolaan Penyediaan Air Minum Perdesaan Dan Implikasinya Terhadap Ketahanan Lingkungan Wilayah (Studi Di Kabupaten Buleleng, Provinsi Bali) - Kerta Arsana, I Gusti Ngurah; Yekti, Mawiti Infantri; Astiti, Sagung Putri Chandra (Universitas Gadjah Mada, 2024)
ABSTRACT Rural drinking water management in Buleleng Regency was served by rural drinking water supply (PAM Des) and community-based drinking water supply (Pamsimas). Providing sustainable rural drinking water was the most basic need through the implementation of Tri Hita Karana. Tri Hita Karana (THK) as a sustainability concept greatly determined the success of regional environmental resilience. This research aimed to analyzed strategies for increasing the implementation of Tri Hita Karana in sustainability in the management of PAM Des. Analysis of the sustainability index for PAM Des management used the Multi Dimensional Scaling (MDS) method. Multi Dimensional Scaling also analyzed lever factors that were sensitive to sustainability.The results of the analysis showed that the sustainability index value for the ecological dimension was 70.11%, the economic dimension was 46.00%, the socio-cultural dimension was 50.65%, the technological dimension was 46.89% and the institutional dimension was 49.74%. The sustainability index value for the ecological and socio-cultural dimensions with a value above 50% was quite sustainable. The sustainability index value of the economic, technological and institutional dimensions of the less sustainable category. The leverage factors obtained from the analysis of 5 (five) dimensions of sustainability were 19 factors.The strategy to increased the implementation of Tri Hita Karana in the ecological and socio-cultural dimensions was the implementation of mutual exchange between PAM Des managers and land owners of springs, implementation of magpag toya upakara, tumpek wariga, community participation in PAM Des, use of water according to needs, adjustment of the level of community water needs and community concern for PAM Des infrastructure. In the economic, technological and institutional dimensions, this must be done by improving, improving the PAM Des infrastructure and also regulations that strengthened the management of PAM Des. The strategy to increased the implementation of Tri Hita Karana had had a positive impact on environmental resilience in the management of rural drinking water supplies in Buleleng Regency, Bali.